PENGARUH PENGEMBANGAN KARIR DAN PEMELIHARAAN TERHADAP EMPLOYEE ENGAGEMENT PADA KARYAWAN DINAS PERUMAHAN, PEMUKIMAN DAN PERTANAHAN KABUPATEN BANDUNG - Widjajanta, Bambang -; Sumiyati, Sumiyati; Baskara, Chedi Cakra (Journal of Business Management Education (JBME), 2020)
The purpose of this study was to measure and analyze the influence of career development and maintenance to employee engagement of employees in the Dinas Perumahan, Pemukiman, dan Pertanahan (Disperkimtan) Kabupaten Bandung. The research design used path analysis method by collecting data through a questionnaire from samples of 90 employees of the Disperkimtan Kabupaten Bandung. The design of this research used descriptive and verification data analysis techniques that also discussed the relationship between variables. The results showed the measurements of career development, maintenance of employees, and employee engagement of Disperkimtan Kabupaten Bandung were in a good category. Meanwhile the career development and maintenance of employees had influence to employee engagement of Disperkimtan Kabupaten Bandung. Career development had a low influence in employee engagement, and maintenance of employees had sufficient influence in the employee engagement of Disperkimtan Kabupaten Bandung.